(untitled) (Medical Forum Monthly, 2024)
Objective: This study aimed to compare the effectiveness of rifaxamin versus norfloxacin in prevention of spontaneous bacterial peritonitis in cirrhotic patients. Study Design: Randomized Control Trial. Place and Duration of Study: This study was conducted at the Medical Unit-II, Shaheed Mohtarma Benazir Bhutto Medical University, Larkana from January, 2019 to June, 2019. Materials and Methods: All patients who fulfilled the inclusion criteria and visited to the Medical unit-II, Chandka Medical College and Hospital, SMBBMU Larkana were included in the study. Informed consent was taken after explaining the procedure, risks and benefits of the study. The total of 244 patients were randomly divided into two groups i.e. (Group A Rifaxamin) and (Group B Norfloxain). Ascitic tap was done to all the patients to see the presence of SBP and blood samples weresent to the laboratory for urea, creatinine, serum sodium, serum bilirubin, serum albumin and PT. Patients were followed over the duration of 6 months and each patient was called for examination after every 3 months to assess the efficacy in term of non-reoccurrence of SBP. All the collected information was recorded on proforma and used electronically for research purpose. Results: Mean ± SD of age was 37.74±8.75 and 38.89±8.84 years in norfloxacin and rifaximin group respectively. In group wise distribution of gender 64 (52.5%) male and 58 (47.5%) female was enrolled in norfloxacin group and 74 (60.6%) male and 48 (39.4%) female was included in rifaximin group. In comparison of both groups 103(84.4%) efficacy was noted in norfloxacin group whereas 110(90.2%) efficacy was documented in rifaximin groupand p value found to be insignificant i.e. (P=0.178). Conclusion: As non-significant difference was found between rifaximin versus norfloxacin, so it is to be concluded that rifaximin is an appropriate alternative for long-term primary and secondary prophylaxis of SBP in cirrhotic patients with ascites.